'We will not move' from the Old Location to Katutura: Forced Resettlement in Windhoek, South West Africa (1959-1968) (Historia, 2023)
Until the early 1960s the Windhoek Main Location (now called the Old Location) was the biggest African urban settlement in South West Africa/Namibia. Being situated close to the centre of town, residents had easy access to their places of work. However, with the further entrenchment of spatial segregation under apartheid, plans for a relocation into a newly created township at the margins of the city gradually took shape in the early 1950s and were implemented by the late 1950s. But residents refused to abandon the accommodation they owned to move to rented houses far away from town. Their protest against relocation provoked a massacre on 10 December 1959. As of 1960, the township Katutura became the new settlement and has expanded since then. This article recapitulates the steps towards the relocation despite growing opposition from residents and the Native Advisory Board. Based on documents in the Namibian National Archive and at the Basler Africa Bibliographien, this account of the last steps towards the closure of the location adds to previous work and is part of a more general social history, hitherto not yet in the public domain.
Keywords: Windhoek Main Location; Windhoek Old Location; Windhoek Municipality; 10 December massacre; Katutura; Native Advisory Board; forced resettlement